Involvement of Specialist Palliative Care in a Stroke Unit in Austria—Challenges for Families and Stroke Teams - Riesinger, Renate; Altmann, Klaus; Lorenzl, Stefan (Frontiers in Neurology, 2021)
Abstract Purpose: Severe stroke poses vast challenges. Appropriate goals of care according to individual preferences and values have to be developed under time restrictions – often impeded by limited ability to communicate and the need for decisions by surrogates. The aim of our study was to explore the decision-making process and the involvement of specialist palliative care in the acute phase of severe stroke. Methods: Twenty patients suffering from severe ischemic stroke treated in an Austrian acute inpatient stroke unit were included in a prospective study. Their families were interviewed with a questionnaire (FS-ICU 24), which covered satisfaction with care and decision-making. With a second questionnaire, decision-making processes within the stroke team were investigated. Results: A palliative approach and early integration of specialist palliative care in severe ischemic stroke results in individualized therapeutic goals, including withholding therapeutic or life-sustaining measures, especially in patients with pre-existing illness. Conclusions: Family members benefit from understandable and consistent information, emotional support and a professional team identifying their needs. Stroke unit professionals need skills as well as knowledge and strategies in order to make decisions and provide treatment at the end-of-life, when there may be ethical or legal issues. Close cooperation with specialist palliative care services supports both treatment teams and families with communication and decision-making for patients with severe ischemic stroke.